Picture Exchange Communication System (PECS) dan Communication Apprehension (CA) pada Remaja Tunagrahita Jenjang SD di SLBN Salatiga - Happy Cahyani Sunusi; Chr. Hari Soetjiningsih; A. Ign. Kristijanto (Jurnal Psikologi, 2018)
The purpose of this study was to examine the influence of PECS on verbal communication skills of adolescent tunagrahita and test the difference of anxiety verbal communication adolescent tunagrahita based on gender. Experimental design for verbal communication skills used Analysis of Covariance with Randomized Completely Block Design (RCBD) based on 6 phases of pre and post-test. The subjects of this research were seven elementary students. Data collection used the Measure of Elementary Communication Apprehension (MECA) questionnaire and be analyzed using Covariance Analysis, verbal communication anxiety pre, and post-test analyzed by Wilxocon and the difference verbal communication anxiety by sex analyzed by Mann Whitney U. The results of this study show that PECS can improve verbal communication skills and affect verbal communication anxiety in elementary school adolescent with intellectual disability and also differ based on sexAbstrak: Tujuan penelitian ini adalah untuk menguji pengaruh PECS terhadap keterampilan kemampuan komunikasi verbal remaja tunagrahita dan menguji perbedaan kecemasan komunikasi verbal remaja tunagrahita berdasar jenis kelamin. Desain eksperimen untuk data keterampilan komunikasi verbal menggunakan analisis Dwi Ragam dengan rancangan dasar RAK (Rancangan Acak Kelompok) berdasarkan enam tahapan pra dan paska uji. Partisipan penelitian sebanyak tujuh siswa SD. Alat pengumpulan data menggunakan kuesioner Measure of Elementary Communication Apprehension (MECA) selanjutnya menggunakan Analisis Dwi Ragam, uji perbedaan kecemasan komunikasi verbal pra dan paska uji menggunakan uji Wilxocon dan uji perbedaan kecemasan komunikasi verbal berdasar jenis kelamin menggunakan uji Mann Whitney U. Hasil yang ditemukan PECS dapat meningkatkan keterampilan komunikasi verbal dan juga kecemasan komunikasi verbal pada remaja tunagrahita jenjang SD berdasar jenis kelamin.